2012
DOI: 10.1021/la300346t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Colloidal Fluorescent Silver Nanoclusters

Abstract: Ultrasmall water-soluble silver nanoclusters are synthesized, and their properties are investigated. The silver nanoclusters have high colloidal stability and show fluorescence in the red. This demonstrates that like gold nanoclusters also silver nanoclusters can be fluorescent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 74 publications
1
30
1
Order By: Relevance
“…We can broadly classify luminescent Ag NCs that have been successfully synthesized into two types: (1) macromoleculeprotected luminescent Ag NCs (for example, polymers, [37][38][39] dendrimers, 40 DNA [41][42][43] and proteins 44,45 ) and (2) thiol-protected luminescent Ag NCs. [46][47][48][49][50][51][52] Among the luminescent Ag NCs, thiolprotected Ag NCs are more attractive for biomedical applications, especially for subcellular imaging, because of their ultrasmall hydrodynamic diameters (o3 nm), facile post-functionalization and good stability. Thiol-protected Ag NCs are generally synthesized by the etching or decomposition method by making use of the unique thiol-Ag interaction, where large-sized non-luminescent nanocrystals or NCs are etched by thiol ligands to smaller-sized luminescent NCs with a well-defined structure.…”
Section: Introductionmentioning
confidence: 99%
“…We can broadly classify luminescent Ag NCs that have been successfully synthesized into two types: (1) macromoleculeprotected luminescent Ag NCs (for example, polymers, [37][38][39] dendrimers, 40 DNA [41][42][43] and proteins 44,45 ) and (2) thiol-protected luminescent Ag NCs. [46][47][48][49][50][51][52] Among the luminescent Ag NCs, thiolprotected Ag NCs are more attractive for biomedical applications, especially for subcellular imaging, because of their ultrasmall hydrodynamic diameters (o3 nm), facile post-functionalization and good stability. Thiol-protected Ag NCs are generally synthesized by the etching or decomposition method by making use of the unique thiol-Ag interaction, where large-sized non-luminescent nanocrystals or NCs are etched by thiol ligands to smaller-sized luminescent NCs with a well-defined structure.…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance maximum for the AgNCs appears at 360 nm. Such damping of surface plasmon absorption with a corresponding weak and broadened absorption is a characteristic of nanoclusters with a size of around 2 nm . The absence of a band at around 400 nm, which is a characteristic surface plasmon resonance band of silver nanoparticles, indicates the formation of the nanocluster .…”
Section: Resultsmentioning
confidence: 99%
“…Now for hollow Au nanoparticles the shell layer thickness is $10-12 nm and the shell layer is formed by the deposition of 5-7 nm sized Au particles, whereas in case of hollow Ag/Au nanoparticles the individual shell layer thickness is near to 2 nm. In previous literatures it was observed that small sized Au and Ag nanoparticles are highly active to absorb and emit light [37][38][39], so these small size particles show strong SPR, and the fluorescence bands for Au and Ag nanoparticles are in the visible and NIR regions, respectively. Finally, the hollow Ag/Au nanoparticles show the cumulative optical effect of both Au and Ag with increased intensities of absorbed and emitted lights.…”
Section: Optical Properties Of Hollow Au and Hollow Bi-metallic Nanopmentioning
confidence: 99%